Composites The analysis of the reason why our bones are created as composite material via comparing other materials: why our bones are created as composite material (International Journal of Scientific Research and Management (IJSRM), 2020)
In this study, the reasons why the bones, which make up the skeletal system and were subjected to continuous compression, were created as a natural composite structure were investigated. They had been compared by being subjected to compression test separately together with sheep bone, wood, plastic and steel pipes prepared in the same dimensions. Thus, the advantages of being a composite material of the bone to our body were investigated by comparing with other materials; the data obtained from the experiments were evaluated and reported. Besides the results obtained from after the compression tests were supported by using the graphics and photographs.